Pengembangan Media Pembelajaran Interaktif dalam Pendidikan Agama Islam: Tren dan Tantangan - Lasmana, Galih (Lembaga Pengkajian Pengembangan Pendidikan dan Kewirausahaan, 2024)
In today's digital era, interactive learning media plays an important role in education, including in Islamic religious education. This journal explores the development of interactive learning media in the context of Islamic religious education, focusing on the latest trends and challenges faced. The research method used is a literature review and trend analysis by reviewing various literature, articles, and sources related to learning media. The results of the study indicate that although there are various innovations in interactive learning media, challenges such as limited access to technology and cultural diversity still need to be overcome. This article is expected to provide insight for educators and learning media developers to optimize the use of technology in Islamic religious education.